Mantle Plumes A Multidisciplinary Approach - Ritter, Joachim R. R.; Christensen, Ulrich R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The concept of mantle plumes, originally suggested by Morgan (1971), is widely but not unequivocally accepted as the cause for hotspot volcanism. Plumes are thought of as deep-rooted, approximately cylindrical regions of hot rising mantle rock with a typical diameter of 100-200 km. Pressure-release melting near the b- tom of the lithosphere produces magmas that rise to the surface and lead, when the plate moves relative to the plume, to a chain of volcanic edifices whose age p- gresses with increasing distance from the plume. For a long time, the evidence for mantle plumes has been largely circumstantial. Laboratory and computer models of mantle convection show that under certain conditions plume-like structures can be found, and these simulations have been used to characterise their properties. Geodetic signals, such as topographic swells and associated geoid anomalies which surround the volcanic hotspots, support the plume hypothesis. They are best identified in an oceanic environment where the plume signal is usually less s- ceptible to be masked by effects of crustal or lithospheric heterogeneities. The i- topic and trace element composition of hotspot lavas differs from those of m- oceanic ridge basalts which is interpreted as indication for a source reservoir d- ferent from average upper mantle rock. The idea of mantle plumes has gained widespread popularity in various disciplines of Earth science and has been used, sometimes perhaps excessively, to explain volcanic and other phenomena.
Basic Properties of Mantle Plumes -- Fluid Dynamics of Mantle Plumes -- Case studies -- Tracing the Hawaiian Mantle Plume by Converted Seismic Waves -- Iceland: The current picture of a ridge-centred mantle plume -- Combined Gas-geochemical and Receiver Function Studies of the Vogtland/NW Bohemia Intraplate Mantle Degassing Field, Central Europe -- Crustal and Upper Mantle Structure of the French Massif Central Plume -- Eifel Region -- Geodynamic Setting of the Tertiary Hocheifel Volcanism (Germany), Part I: 40Ar/39Ar geochronology -- Geodynamic Setting of the Tertiary Hocheifel Volcanism (Germany), Part II: Geochemistry and Sr, Nd and Pb Isotopic Compositions -- The Quaternary Volcanic Fields of the East and West Eifel (Germany) -- Thermal and Geochemical Evolution of the Shallow Subcontinental Lithospheric Mantle Beneath the Eifel: Constraints from Mantle Xenoliths, a Review -- He-Ne-Ar Isotope Systematics of Eifel and Pannonian Basin Mantle Xenoliths Trace Deep Mantle Plume-Lithosphere Interaction Beneath the European Continent -- Quaternary Uplift in the Eifel Area -- The Seismic Signature of the Eifel Plume -- Upper Mantle Structure Beneath the Eifel from Receiver Functions -- Rayleigh Wave Dispersion in the Eifel Region -- Seismic Anisotropy in the Asthenosphere Beneath the Eifel Region, Western Germany -- Gravity Observations in the Western Rhenish Massif and Forward Modelling of the Eifel Plume Bouguer Anomaly.
Keywords: Earth sciences; Inorganic chemistry; Geology; Geophysics; Physics; Earth Sciences; Geophysics/Geodesy.; Inorganic Chemistry; Geology; Theoretical, Mathematical and Computational Physics; Electronic books